Science Learning Outcomes with Numbered Heads Together and Audiovisual Media: Hasil Pembelajaran Sains dengan Metode Numbered Heads Together dan Media Audiovisual - Aslamiyah; Sundahry; Randi Eka Putra (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Science learning in Indonesian elementary schools often faces challenges related to low student engagement and achievement, as reflected in declining PISA scores. Specific Background: At SDN 064/II Perumnas I, fourth-grade students demonstrated limited participation and low mastery of science (IPAS), with only 30.77% achieving the school’s minimum competency standard. Knowledge Gap: Traditional lecture-based teaching remains dominant, providing little room for active, collaborative, and meaningful learning, and few studies have explored combining cooperative learning with audiovisual media in IPAS at the primary level. Aims: This study aimed to improve student learning outcomes and engagement in science through the Numbered Heads Together (NHT) cooperative model supported by audiovisual media. Results: Conducted as Classroom Action Research with 13 students over two cycles, the study showed an increase in mastery from 76.92% in Cycle I to 100% in Cycle II, accompanied by improved teacher performance and higher student participation in group discussions. Novelty: The integration of NHT with audiovisual media presents an innovative approach that optimally addresses the cognitive and social learning needs of elementary students. Implications: The findings suggest that this combined strategy is effective for fostering active participation, critical thinking, and improved academic achievement in science, and it can be recommended for broader application in primary education.Highlight : Student engagement and participation in science learning increased. Learning outcomes improved from 76.92% in Cycle I to 100% in Cycle II. Teacher performance and learning process became more effective. Keywords : Learning Outcomes, Numbered Heads Together Model, Audiovisual Media, Science Learning, Cooperative Learning